Operational Excellence for Innovative and Purposeful Business for Student Study Of Independent Project at Pt Paragon Technology And Innovation to Create Business Plan Baby Skincare - Luis Fernando Sihombing; Amlys Syahputra Silalahi; Khaira Amalia Fachrudin; Beby Kendida Hasibuan (Journal Of Management Analytical and Solution (JoMAS), 2022)
This study aims to determine operational excellence for innovative and purposeful business for students of independent projects at PT Paragon Technology and Innovation. The type of research used is descriptive analysis method with a qualitative approach. The data used in the form of primary data and secondary data. The final project of joining this Independent Project is implemented into an innovative and purposeful business to create amore natural rich cream, a baby skincare business with natural ingredients and innovating by replacing parabens with leuconostoc fermented as a first bio representative first in Indonesia. Human resource management strategy of study of independent project in this Amore Natural Rich Cream business by applying manpower planning. Where manpower planning is a plan for recruiting human resources in this business by taking into account the qualifications and number of workers needed to make this business run and according to plan. Strategic leadership Students from this business plan is to apply pestel analysis by monitoring the business environment before the business is launched which is seen from the Political, Economic, Social, Technological, Environmental, and Legal aspects. In addition to the PESTEL analysis, it also performs a porters five force. Supply chain management is implemented concept of plan, source, make, deliver, store and customer as well as analyzing demand and production planning. The financial aspect of this business plan is by conducting an investment analysis of the results obtained that this business requires an initial investment as the overall working capital for this business where all this investment is borne 100% from PT Paragon Technology and Innovation. From the results and discussions that have been carried out the investment assessment shows that the discounted payback period (DPP) of the investment plan is 2 years 5 months where investors set a maximum payback period of 4 year. The net present value (NPV) of the investment plan has a positive value of Rp3.358.277.304. The IRR value of the investment plan is 25% greater than the required interest rate of 15The profitability Index (PI) of the investment plan is greater than 1 (PI > 1). From the investment analysis investment business plan baby skincare is profitable if implemented.